A Case Study of Experiences with Transmediation for a Student with Learning Disabilities - Chang, Lisa; Asselin, Marlene (Language and Literacy / Langue et littératie, 2023)
This case study explored the experiences with transmediation by a fourth grade student with learning disabilities (LD) and his teacher. Findings revealed that the student encountered mixed responses to his practices by the classroom community. Underlying these perspectives were issues of social capital contributing to the power dynamics of the classroom, and two contrastive provincial curriculum documents guiding classroom literacy instruction and assessment. Drawing on these findings, we discuss the nuances and complexities of transmediation for students with diverse learning needs.